RISK FACTORS AND PREVENTIVE STRATEGIES OF BREAST CANCER AMONG WOMEN IN TRANSITIONAL HEALTHCARE SYSTEMS (Global Conference on Multidisciplinary Research and Innovation, 2026)
Breast cancer remains one of the most significant oncological challenges affecting women worldwide. While global incidence rates continue to rise, transitional healthcare systems, including those in Central Asia, are facing increasing disease burden due to demographic shifts, lifestyle changes, and limited early screening coverage. Understanding risk factors and implementing effective preventive strategies are essential components of reducing breast cancer morbidity and mortality.
Keywords: Breast cancer; risk factors; prevention strategies; BRCA mutations; lifestyle factors; screening programs; early detection; public health; women’s health; oncology in developing countries.